Natural Gas Market Liberalization: An Examination of UK and US Futures and Spot Prices - Simpson, John (Springer-Verlag Berlin Heidelberg, 2013)
The study reported in this chapter builds on previous studies of the extent of decoupling of oil and gas markets and thus the degree of deregulation of the gas sector in each country. It examines both UK and US oil and gas spot and futures market data. Spot gas and gas futures data from the respective domestic markets represent domestic factors and oil prices from global datasets represent global factors. Cointegration and exogeneity tests indicate that US markets have achieved a greater degree of decoupling with domestic gas price factors dominating global oil price factors in the determination of the future spot gas price. Therefore, it can be concluded that whilst progress in liberalization has been made in both markets, US deregulation policies have been more effective than those in the UK.